2D Metal Organic Framework‐Graphitic Carbon Nanocomposites as Precursors for High‐Performance O2‐Evolution Electrocatalysts. Issue 35 (26th October 2018) - Rodenas, Tania; Beeg, Sebastian; Spanos, Ioannis; Neugebauer, Sebastian; Girgsdies, Frank; Algara‐Siller, Gerardo; Schleker, Peter Philipp Maria; Jakes, Peter; Pfänder, Norbert; Willinger, Marc; Greiner, Mark; Prieto, Gonzalo; et al.
Abstract: The development of effective and precious‐metal‐free electrocatalysts for the oxygen evolution reaction (OER) represents a major bottleneck to unlock a renewable energy scenario based on water splitting technologies. Materials uniting the electrical conductivity of conjugated graphitic nanomaterials with the chemical regularity of metal‐organic‐framework (MOF) crystals are promising precursors for such electrocatalysts. Nanoscale integration of these two materials is challenging. A new synthesis route is developed that integrates 2D MOF nanocrystals and graphitic carbon nanolamellae into layered composites. The graphitic carrier contributes excellent charge–transport properties, and the 2D macromolecular MOF precursor provides a suitable shuttle for introducing highly dispersed metal species. Furthermore their direct chemical environment can be controlled via selection of organic linker. Thermal decomposition of 2D cobalt tetrafluoro benzene‐dicarboxylate MOF nanocrystals within such composites enables the stabilization of cobalt oxyhydroxyfluoride nanoparticles on the graphitic carrier, which display an extraordinary activity for the OER in alkaline media, with low onset overpotential (310 mVRHE ) and current densities >10 4 mA cm −2 μmolCo −1 at an operating overpotential of 450 mV, alongside excellent operational stability. The wide compositional array of MOFs makes this synthesis approach versatile toward advanced (electro)catalysts and other functional materials for applications from sensing to energy storage and conversion. Abstract : A highly active and stable precious‐metal‐free electrocatalyst for the oxygen evolution reaction (OER) is synthesized by the integration of 2D graphitic and reticular metal‐organic‐framework (MOF) precursors into heterostructured composites, combining excellent conductivity with fine dispersed active cobalt species.